CRASH TEST ANALYSIS OF IMPACT BARRIER USING HONEY COMB TEXTILE AND OTHER GEOMETRY’S BY USING COMPOSITES - Naresh, P.; Babu, A.V. Hari; Babu, S.Ramesh; Reddy, M. Sudhakar; Reddy, Dr.P.Malli Karjuna (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Textile honeycomb composites, with an array of hexagonal cells in the cross section, is a type of textile composites having the advantage of being light weight and energy absorbent over the solid composite materials. The aim of this project is to investigate the influence of the geometric parameters on textile honeycomb composites on their mechanical performances under low velocity impact, which can be used to help designer control over the textile honeycomb composites. The 3D honeycomb fabrics are successfully manufactured and converted into textile honeycomb composites. It was found through the finite element analysisTextile honeycomb composites, with an array of hexagonal cells in the cross section, is a type of textile composites having the advantage of being light weight and energy absorbent over the solid composite materials. The aim of this project is to investigate the influence of the geometric parameters on textile honeycomb composites on their mechanical performances under low velocity impact, which can be used to help designer control over the textile honeycomb composites. The 3D honeycomb fabrics are successfully manufactured and converted into textile honeycomb composites. It was found through the finite element analysis (FEA) that changes in geometric and structural parameters of the textile honeycombcomposites have noted influences on the energy absorption, force attenuation and damage process of the structure. This project carries the comparision betweenhoneycomb,hexagonal,box,triangule r and cross trianguler composite shapes for optimized inner core design based on FEA based impact analysis to rectify the delamination problems occoring in hony comb technology due to impacts (even small impacts).